Drought, climate change and vegetation response in the succulent karoo, South Africa - M. Hoffman; P. Carrick; L. Gillson; A. West (South African Journal of Science, 2009)
For the winter-rainfall region of South Africa, the frequency of drought is predicted to increase over the next 100 years, with dire consequences for the vegetation of this biodiversity hotspot. We analysed historical 20th century rainfall records for six rainfall stations within the succulent karoo biome to determine if the signal of increasing drought frequency is already apparent, and whether mean annual rainfall is decreasing. We found no evidence for a decrease either in mean annual rainfall or in the incidence of drought, as measured by the Standardised Precipitation Index (SPI) over the 20th century. Evidence points to a drying trend from 1900 - 1950 while no significant trend in rainfall and drought was found at most stations from 1951 - 2000. In a second analysis we synthesised the information concerning the response of adult succulent karoo biome plants and seedlings to extended drought conditions. General findings are that responses to drought differ between species, and that longevity is an important life history trait related to drought survival. Growth form is a poor predictor of drought response across the biome. There was a range of responses to drought among adult plants of various growth forms, and among non-succulent seedlings. Leaf-succulent seedlings, however, exhibited phenomenal drought resistance, the majority surviving drought long after all the experimentally comparative non-succulent seedlings had died. Our synthesis showed that previous studies on the impact of drought on succulent karoo biome plants differ greatly in terms of their location, sampling design, measured values and plant responses. A suite of coordinated long-term field observations, experiments and models are therefore needed to assess the response of succulent karoo biome species to key drought events as they occur over time and to integrate this information into conservation planning.